Preparation, Evaluation, and In Vitro Antiacne Activity of Cymbopogon citratus DC and Cymbopogon nardus (L.) Rendle Essential Oil Microemulsion - Datubara, Martaulina Elisabet; Kumala, Shirly; Rahmat, Deni (Faculty of Pharmacy Universitas Pancasila, 2023)
This study was conducted to formulate and evaluate a topical anti-acne microemulsion containing essential oils of Cymbopogon citratus DC and Cymbopogon nardus (L). Using the disc diffusion method, the antibacterial activity of the essential oils of C. citratus and C. nardus against Propionibacterium acne and Staphylococcus epidermidis was investigated. After identifying the active concentration, the formula for a topical microemulsion was devised and tested for physical and chemical parameters. The results revealed that the essential oils of C. citratus and C. nardus had antimicrobial activity against P. acnes and S. epidermidis. The results demonstrated that the obtained microemulsion meets the physical and chemical requirements and possesses antimicrobial activity. It can be concluded that the essential oils extracted from C. citratus and C. nardus have the potential for further development and commercial application in the treatment of acne.